2018
DOI: 10.3390/w10101299
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Site-Specific BMPs Using a Spatially Explicit, Field-Scale SWAT Model with Edge-of-Field and Tile Hydrology and Water-Quality Data in the Eagle Creek Watershed, Ohio

Abstract: The Eagle Creek watershed, a small subbasin (125 km2) within the Maumee River Basin, Ohio, was selected as a part of the Great Lakes Restoration Initiative (GLRI) “Priority Watersheds” program to evaluate the effectiveness of agricultural Best Management Practices (BMPs) funded through GLRI at the field and watershed scales. The location and quantity of BMPs were obtained from the U.S. Department of Agriculture-Natural Resources Conservation Service National Conservation Planning (NCP) database. A Soil and Wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Modeling suggests that filter strips are the most effective stand‐alone BMP for reducing DRP, whereas cover crops were the most effective stand‐alone BMP for reducing winter DRP loading (Merriman et al, 2018). However, cover crops have been implicated as being sources of DRP, as P from plants can be mobilized in runoff (Lozier et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Modeling suggests that filter strips are the most effective stand‐alone BMP for reducing DRP, whereas cover crops were the most effective stand‐alone BMP for reducing winter DRP loading (Merriman et al, 2018). However, cover crops have been implicated as being sources of DRP, as P from plants can be mobilized in runoff (Lozier et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported high removal rates of sediment and nutrients in surface flows through the use of filter strips [63,64]. In their study conducted in Iran, Babaei et al [63] found filter strip to be a very effective BMP in reducing total nitrogen load (42.61%), and total phosphorus load (39.57%).…”
Section: Filter Strip Scenariomentioning
confidence: 99%
“…Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017). Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017).…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%
“…Assessing benefits of agricultural BMPs is challenging due to the multiple impacts on hydrology, nutrient cycling, soil fertility, and other processes. Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017). BMPs that slow runoff are effective in reducing sediment detachment and transport (Bosch et al 2013;Mitchell et al 2018), although effectiveness can vary depending on watersheds characteristics, BMPs location, and storm magnitude.…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%